Historical Development of SHRM: Bibliometric Analysis of SHRM Based On Web of Science - Gürol, Yonca; Sarp, Pinar; Atila, Muhammet; Yeke, Selçuk; Binici, Ceylan Merve (Universiti Utara Malaysia Press, 2024)
In the study, 2,220 articles related to the concept of Strategic Human Resources Management (SHRM) published in the period of 1980-2020 and included in the SCI, SSCI and ESCI citation indexes were examined bibliometrically on the Web of Science database using the VOSviewer software. The purpose of the study is to essentially evaluate the studies conducted with the concept of SHRM and provide foresight for future studies. In this context, in order to evaluate the publications in the study, the changes in the number of publications in the publication volume in the field were discussed, the developments in the field, the trends in the subject headings, the countries and institutions that make the strongest contribution to the literature, the field and the most cited ones in the field were examined. The results indicated that the number of studies on the concept of strategic human resources increased in the 2000s. The acceleration in the number of studies is noteworthy, especially in 2015 and after. It is seen that frequently used keywords in the field of strategic human resources are strategy, strategic management, human resource, and performance. Other keywords with high connection strength are listed as human capital, knowledge management, strategic management, dynamic capabilities, high-performance work system and HR development. It is recommended that future researchers should carry out empirical and conceptual studies on the reasons for the differences in the number of studies published by countries in the field of SHRM and their level of interest in the field.